2021
DOI: 10.2196/28210
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Feasibility of Early Mobilization With Virtual Reality Gaming Using Head-Mounted Display and Adaptive Software With Adolescents in the Pediatric Intensive Care Unit: Case Report

Abstract: Background Early rehabilitative mobilization for adolescents is safe and feasible. However, there is a lack of published rehabilitation strategies and treatments that can maximize engagement and outcomes among adolescents in the pediatric intensive care unit (PICU). Virtual reality (VR) gaming using a head-mounted display (HMD) and adaptive software can allow active and nonactive gameplay at the bedside for people with limited arm mobility, making it a potentially inclusive and enjoyable treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…92% of parents reported that VR calmed their children, and 78% of participants felt that VR was calming. HRVi Minimum scores were significantly higher during VR Lai et al (2021, United States) * [ 58 ] 2 Case report 4 PICU patients Case 1:15 Case 2: 13 Case 1: 18 min (SD 11) per session, 4 sessions Case 2: 35 min (SD 7) per session, 2 sessions Between usual care, when tolerable and requested by the participant VR gaming sessions with active games (e.g., boxing, rhythmic movement to music, and exploratory adventure) and nonactive games (e.g., racing and narrative adventure) n/a The findings of this study suggest that VR gaming with HMDs and adaptive software is likely a feasible supplement to usual care for adolescents within the PICU, and these findings warrant further investigation. Recommendations for future studies aimed at incorporating VR gaming during early mobilization are presented herein Hemphill et al (2021, United States) [ 73 ] 1 Case report 4 Pediatric ICU patient n/a n/a During physical therapy sessions VR to encourage the child to engage in physical therapy sessions n/a Virtual reality encouraged the child to engage in physical therapy sessions, participate for greater durations, and directly address barriers to discharge Scapin et al (2017, Brazil) [ 84 ] 2 Case report 4 Pediatric burn patients 8, 9 15 min, 35 min, 25 min Dressing change during balneotherapy The child used VR to watch a game that simulated a roller coaster n/a The use of goggles was easy to apply and well-accepted by the children, and had a relevant effect reducing pain (pain face: case 1: 10/10 during a dressing change, 4 during VR use vs. case 2: 4 during dressing; 0 during use VR,) Kucher et al (2020, United States) * [ 56 ] 6 (6/0) Proof-of-concept study ...…”
Section: Resultsmentioning
confidence: 99%
“…92% of parents reported that VR calmed their children, and 78% of participants felt that VR was calming. HRVi Minimum scores were significantly higher during VR Lai et al (2021, United States) * [ 58 ] 2 Case report 4 PICU patients Case 1:15 Case 2: 13 Case 1: 18 min (SD 11) per session, 4 sessions Case 2: 35 min (SD 7) per session, 2 sessions Between usual care, when tolerable and requested by the participant VR gaming sessions with active games (e.g., boxing, rhythmic movement to music, and exploratory adventure) and nonactive games (e.g., racing and narrative adventure) n/a The findings of this study suggest that VR gaming with HMDs and adaptive software is likely a feasible supplement to usual care for adolescents within the PICU, and these findings warrant further investigation. Recommendations for future studies aimed at incorporating VR gaming during early mobilization are presented herein Hemphill et al (2021, United States) [ 73 ] 1 Case report 4 Pediatric ICU patient n/a n/a During physical therapy sessions VR to encourage the child to engage in physical therapy sessions n/a Virtual reality encouraged the child to engage in physical therapy sessions, participate for greater durations, and directly address barriers to discharge Scapin et al (2017, Brazil) [ 84 ] 2 Case report 4 Pediatric burn patients 8, 9 15 min, 35 min, 25 min Dressing change during balneotherapy The child used VR to watch a game that simulated a roller coaster n/a The use of goggles was easy to apply and well-accepted by the children, and had a relevant effect reducing pain (pain face: case 1: 10/10 during a dressing change, 4 during VR use vs. case 2: 4 during dressing; 0 during use VR,) Kucher et al (2020, United States) * [ 56 ] 6 (6/0) Proof-of-concept study ...…”
Section: Resultsmentioning
confidence: 99%
“…Increasing peak oxygen uptake values with AVGs could prevent the disease-associated loss of autonomy and allow the patient to live independently as a healthy individual. AVGs, through their repetitive and rapid movements, lead to PA of sufficient intensity to generate adaptations in pathological individuals, demonstrating the relevance of AVGs as a rehabilitation strategy [ 23 , 26 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although VR has been used in a variety of clinical settings for symptoms management (eg, pain and anxiety) [ 36 , 37 ], to the best of our knowledge, this study was the first to test the Meta Quest 2 as a home-based method for web-based group socialization among adolescents with physical disabilities. The implementation of the intervention was successful.…”
Section: Discussionmentioning
confidence: 99%